Analisis Ketersediaan Fasilitas di Objek Wisata Pantai Nirwana Kota Baubau - Nuryadin, Muhammad Azhar; Sugiri, Agung (Teknik PWK (Perencanaan Wilayah Kota), 2023)
Touris facilities are an important aspect that must be considered in tourism development because it can provide tourists encouragement to travel. This study aims to identify the state of tourist facilities that are currently available on Nirwana Beach. The analysis method used in this study is descriptive and quantitative method which using scoring analysis. The results showed that based on the type with reference to the synthesis of literature, the available tourist facilities consist of main facilities (food stalls, boat rentals, inns, buoy rentals and fish burning rentals), supporting facilities (lodging, parking, trash cans, public toilets, worship, coast guard posts, visitor counters, bus stops, gazebos), as well as supporting facilities in the form of information boards and markers. Overall, the provision of tourist facilities at Nirwana Beach is in the almost good category with an average value of 3.43 according to tourists. Some tourist facilities have poor supply conditions based on the existing provision and the perception of tourists such as food stalls, inns, trash cans, worship, coast guard posts, counters, and sign boards. Fishing equipment rental facilities, gift shops and information centers are not yet available in their existing conditions but should be available at a beach tourism object.